Response of Dry Bean to Nitrogen Fertilization and Inoculation with Rhizobium Tropici and Azospirillum Brasiliensis - Vieira, Nilson Darlan; Moreira, Adonis; Moraes, Larissa A. C.; Cerezini, Paula; Soares Filho, Cecilio Viega [UNESP]; Cardoso, Bruna Miguel (Taylor & Francis Inc, 2020)
The dry bean (Phaseolus vulgaris L.) has significant economic importance in Brazil and is one of the most important sources of income, especially for small producers. This study aimed to evaluate the response of dry bean to different nitrogen (N) sources, using a completely randomized design, with five replicates. Treatments comprised five N sources [ammonium sulfate [(NH4)(2)SO4], calcium nitrate [Ca(NO3)(2)], potassium nitrate (KNO3), ammonium nitrate (NH4NO3), and urea] applied at 300 mg kg(-1) N plus three additional treatments (inoculation with Rhizobium tropici, inoculation with R. tropici plus Azospirillum brasiliensis, and the control without N and inoculation). The yield components [grain yield (GY), shoot dry weight yield (SDWY), number of pods per pot (NPP), number of grains per pot (NGPt), pod weight (PW), and number of grains per pod (NGP)], and physiological components [water use efficiency (WUE), photosynthetic rate (A), and stomatal conductance (g(s))] were evaluated. Inoculation with R. tropici and R. tropici plus A. brasiliensis did not induce significant effects on yield components when compared to those of the control. (NH4)(2)SO4 did not change the performance of most quantified yield components, whereas NH4NO3 showed increases in GY, SDWY, NPP, NGP, and PW as well as in WUE. KNO3 and Ca(NO3)(2) resulted in increased performance of GY, SDWY, NPP, A, and g(s) compared to that in the control treatment and the isolated inoculant and its combination with A. brasiliensis. The amide source via urea showed the greatest increase in GY, with 56.5% more than that in the control.
Keywords: Phaseolus vulgaris; nitrogen fertilizers; Rhizobium tropici; Azospirillum brasiliensis; grain yield